The Contribution of Christian Religious Education (CRE) in Achieving Sustainable Development Goals (SDGs) Through a Problem Based Learning Approach - 4A Cycle Model - Wahju Astjarjo Rini; Gracia Paramitha; Yonatan Alex Arifianto; Carolina Etnasari Anjaya; Christian Adi Jaya (Technium Social Sciences Journal, 2024)
Sustainable Development Goals (SDGs) has been an important focus and a common goal for all humanity. Degradation of nature is a concern and responsibility for all areas of life, including education, which is a fundamental factor in developing the quality of human life. In this regard, the aim of this research is to provide some ideas for Christian Religious Education (CRE) at the higher education level in supporting the achievement of the SDGs. This research was conducted by in a qualitative descriptive method. As findings, it is found that the contribution of CRE can be made through Student Centered Learning approach, Inquiry model - problem based learning. This approach is carried out through learning practical matters with stages of achieving targets, which are referred to as the 4A cycle model (Awareness, Action Plan, Actualization and Assimilation).